Analisis Partisipasi Masyarakat dalam Mengurangi Kerusakan Kawasan Hutan Produksi di Kecamatan Polombangkeng Utara Kabupaten Takalar - Tahir, Muh. Zulkifli; Mustapa, Mustapa (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to determine Community Participation and Factors Influencing Community Participation in Reducing Damage to Production Forest Areas in Polobangkeng Utara District, Takalar Regency. The type of research used is descriptive qualitative research. It is said to be qualitative because the main data source in this study is in the form of approaches and actions of people who are observed and interviewed. The location of this research is in Polombangkeng Utara District, Takalar Regency. The research informants are sources who are considered to have extensive knowledge related to the problems being studied, namely the Head of Polombangkeng Utara District, Head of Barugaya Village, Head of Ko'mare Village, Head of Kale Ko'mare Village, Community. The results of the study are Community participation in preventing production forest fires is good, this is evidenced by the involvement, support and responsibility of the community in reducing forest fires. Factors that influence community participation are Community knowledge is more aware of the dangers of forest fires in the environment. Community awareness is good because more people care about production forests.